Leitura literária para bebês e crianças pequenas de 0 a 3 anos de idade: como tem se dado a prática de uma professora no município de Manaus? - Monteiro, Ingrid Magno (Brasil, 2024)
How important is reading to babies and what are its specificities? Based on this guiding question, the first part of this research aims to analyze the academic production published in the form of theses and dissertations in Education, from 2016 to 2018, which had as its object literary reading for babies and children up to three years.This is a bibliographical research, whose focus is the theses and dissertations registered in the CAPES Biblioteca Digital de Teses e Dissertações (BDTD). Literary reading with babies and children up to three years of age has gained greater space for discussion in recent years, although there are still few theses and dissertations dedicated to the topic, especially in the North Region. In addition to the survey and considering this lack of research dedicated to the object, we sought to understand how, in school practices, reading moments with children up to three years of age occur in a daycare center in the city of Manaus.To produce research data, we carried out semi-structured interviews with one of the teachers at the selected daycare center, in addition to participatory observation. Data analysis was based on the contributions of the Philosophy of Language, seeking to observe, in the statements produced by the teacher, which concepts guide her work involving literary reading. The results point to practices that are consistent with what the literature on the subject indicates, positioning children as subjects of enunciation.